2020
DOI: 10.3390/ma13132968
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Study on the Effect of TiN Top and Bottom Electrodes on Atomic Layer Deposited Ferroelectric Hf0.5Zr0.5O2 Thin Films

Abstract: The discovery of ferroelectricity in HfO2-based materials in 2011 provided new research directions and opportunities. In particular, for atomic layer deposited Hf0.5Zr0.5O2 (HZO) films, it is possible to obtain homogenous thin films with satisfactory ferroelectric properties at a low thermal budget process. Based on experiment demonstrations over the past 10 years, it is well known that HZO films show excellent ferroelectricity when sandwiched between TiN top and bottom electrodes. This work reports a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…[ 2,4,5,47–52 ] In this regard, the influence of various bottom electrodes on ferroelectric properties has been extensively studied based on the metal–ferroelectric–metal (MFM) structure. [ 47–51 ] According to the experimental results reported in the past decade, the use of TiN bottom electrodes could be a useful strategy to improve the ferroelectric properties of Hf 1– x B x O 2 films. [ 2,4,47 ] Moreover, it was found that ferroelectric properties, especially endurance, can be further improved by the deposition method of the TiN bottom electrode: >10 10 cycles in ALD TiN and ≈10 9 cycles in sputtered TiN at a pulse amplitude of 2.5 MV cm −1 .…”
Section: Substrate Materials For Low‐thermal‐budget Ferroelectric Fil...mentioning
confidence: 99%
See 1 more Smart Citation
“…[ 2,4,5,47–52 ] In this regard, the influence of various bottom electrodes on ferroelectric properties has been extensively studied based on the metal–ferroelectric–metal (MFM) structure. [ 47–51 ] According to the experimental results reported in the past decade, the use of TiN bottom electrodes could be a useful strategy to improve the ferroelectric properties of Hf 1– x B x O 2 films. [ 2,4,47 ] Moreover, it was found that ferroelectric properties, especially endurance, can be further improved by the deposition method of the TiN bottom electrode: >10 10 cycles in ALD TiN and ≈10 9 cycles in sputtered TiN at a pulse amplitude of 2.5 MV cm −1 .…”
Section: Substrate Materials For Low‐thermal‐budget Ferroelectric Fil...mentioning
confidence: 99%
“…[ 47–51 ] According to the experimental results reported in the past decade, the use of TiN bottom electrodes could be a useful strategy to improve the ferroelectric properties of Hf 1– x B x O 2 films. [ 2,4,47 ] Moreover, it was found that ferroelectric properties, especially endurance, can be further improved by the deposition method of the TiN bottom electrode: >10 10 cycles in ALD TiN and ≈10 9 cycles in sputtered TiN at a pulse amplitude of 2.5 MV cm −1 . [ 54 ] However, to apply these MFM structures directly to electronic device applications, it should be integrated in BEOL rather than FEOL, so a low‐temperature process (<400 °C) is essential (see Figure 2).…”
Section: Substrate Materials For Low‐thermal‐budget Ferroelectric Fil...mentioning
confidence: 99%
“…The same were used in our previous studies. [ 7,11,20,30 ]…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting to note that the reported O‐fe phase content was higher than 50% in case of 1:1 and 1:3 Hf:Zr compositions. Kim et al [ 36 ] found the O‐fe phase was 42.9% in 10 nm Hf 0.5 Zr 0.5 O 2 in MIM stack with TiN electrodes. These differences in the O‐fe phase fractions could be explained by differences in deposition methods, oxygen exposure during HZO deposition, and electrical field cycling.…”
Section: Discussionmentioning
confidence: 99%